1998
DOI: 10.2307/3434228
|View full text |Cite
|
Sign up to set email alerts
|

PM 2.5 and Mortality in Long-Term Prospective Cohort Studies: Cause-Effect or Statistical Associations?

Abstract: Concentrations of ambient PM2.5 (particulate matter c2.5 pm in aerodynamic diameter) were associated with increased mortality in two prospective cohort studies. In this paper, 1 assess whether the weight of the evidence supports a causal association. I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…However, some reviewers of the literature remain troubled by the issue of biological plausibility and argue that there is inadequate consistency across the toxicological and epidemiologic evidence. [495][496][497][498][499] Toxicology is playing a crucial role in understanding the health effects of PM, 500 but there are substantial challenges, especially when it comes to dealing with exposures to complex mixtures. 104,501,502 Another reason for skepticism is at least implied by Phalen 88 in his book dealing with the particulate air pollution controversy.…”
Section: Continued Skepticismmentioning
confidence: 99%
“…However, some reviewers of the literature remain troubled by the issue of biological plausibility and argue that there is inadequate consistency across the toxicological and epidemiologic evidence. [495][496][497][498][499] Toxicology is playing a crucial role in understanding the health effects of PM, 500 but there are substantial challenges, especially when it comes to dealing with exposures to complex mixtures. 104,501,502 Another reason for skepticism is at least implied by Phalen 88 in his book dealing with the particulate air pollution controversy.…”
Section: Continued Skepticismmentioning
confidence: 99%
“…4 People smoking 30 cigarettes a day inhale as much PM 10 as they would if they were continually breathing air containing 24,000 µg/m 3 of PM 10 . 5 There is no consensus as to how PM 10 causes these effects, if indeed it does, 6 or clinical evidence of the damage it causes at these low concentrations.…”
Section: Retired Agronomist New Zealandmentioning
confidence: 99%
“…Given that the ambient PM 10 could add about only 1% to the daily intake of PM 10 by smokers even on highly polluted days, 5 it could be expected that if the extra admissions were caused by inhaling ambient PM 10 , the number of smokers admitted would not have increased on or after high pollution days, as they would not have been affected by the relatively small increases in ambient concentrations. There was no indication that the results for smokers were different from the results for non-smokers.…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Critics of the positive epidemiologic findings consider the disconnect between ambient monitors and actual exposure to be a potential source of error (10,11). However, although some studies have found poor correlations between personal exposure and ambient concentrations (12)(13)(14), the correlations have been stronger when evaluated within individuals across time (15,16).…”
mentioning
confidence: 99%